Unveiling Human Flourishing: A Maqashid Al-Shariah Based Human Development Index in Indonesia - Gunawan, Dedi; Amal, Muhammad Ahsanul; Choiri, Miftakhul (Goodwood Publishing, 2025)
Purpose: This study investigates the influence of the Maqashid al-Shariah framework—covering the protection of religion (Hifzu al-Din), life (Hifzu al-Nafs), intellect (Hifzu al-Aql), progeny (Hifzu al-Nasl), and property (Hifzu al-Mal)—on Indonesia's Human Development Index (HDI). Methodology: The study employs a qualitative approach, using Eviews-12 software for data analysis, particularly utilizing panel data regression techniques. The sample comprises eight Indonesian provinces: Papua, West Papua, East Nusa Tenggara, West Sulawesi, West Kalimantan, West Nusa Tenggara, North Maluku, and Gorontalo, covering the years 2019-2022. Results: The analysis reveals that the protection of religion (Hifzu al-Din) and intellect (Hifzu al-Aql) significantly affect Indonesia's HDI. However, the protection of life (Hifzu al-Nafs), offspring (Hifzu al-Nasl), and property (Hifzu al-Mal) do not show statistically significant direct impacts on HDI. Conclusion: This study concludes that Maqashid al-Shariah’s framework, specifically religion and intellect protection, plays a significant role in enhancing HDI. This research highlights the relevance of integrating Islamic values into human development measures. Limitations: A limitation of this study is the reliance on data from only eight provinces, which may not represent the broader context of Indonesia. Contribution: This research offers a novel perspective by applying the Maqashid al-Shariah framework to assess human development indicators in Indonesian provinces, contributing to the development of an Islamic approach to human development.